Macroeconomic factors and micro-level bank risk - Claudia M. Buch; Sandra Eickmeier; Esteban Prieto (Deutsche Bundesbank, 2010)
The interplay between banks and the macroeconomy is of key importance for financial and economic stability. We analyze this link using a factor-augmented vector autoregressive model (FAVAR) which extends a standard VAR for the U.S. macroeconomy. The model includes GDP growth, inflation, the Federal Funds rate, house price inflation, and a set of factors summarizing conditions in the banking sector. We use data of more than 1,500 commercial banks from the U.S. call reports to address the following questions. How are macroeconomic shocks transmitted to bank risk and other banking variables? What are the sources of bank heterogeneity, and what explains differences in individual banks' responses to macroeconomic shocks? Our paper has two main findings: (i) Average bank risk declines, and average bank lending increases following expansionary shocks. (ii) The heterogeneity of banks is characterized by idiosyncratic shocks and the asymmetric transmission of common shocks. Risk of about 1/3 of all banks rises in response to a monetary loosening. The lending response of small, illiquid, and domestic banks is relatively large, and risk of banks with a low degree of capitalization and a high exposure to real estate loans decreases relatively strongly after expansionary monetary policy shocks. Also, lending of larger banks increases less while risk of riskier and domestic banks reacts more in response to house price shocks.
Keywords: E44; G21; 330; FAVAR; bank risk; macro-finance linkages; monetary policy; microeconomic adjustment; Schock; Makroökonomischer Einfluss; Bankensystem; Bankrisiko; Finanzintermediär; Geldpolitik; Wirtschaftliche Anpassung; VAR-Modell; Schätzung; USA